The Odyssey of Political Theory: The Politics of Departure and Return - Deneen, Patrick J. (Rowman & Littlefield Publishers, 2003)
This path-breaking and eloquent analysis of The Odyssey, and the way it has been interpreted by political philosophers throughout the centuries, has dramatic implications for the current state of political thought. This important book offers readers original insights into The Odyssey and it provides a new understanding of the classic works of Plato, Rousseau, Vico, Horkheimer, and Adorno. Through his analysis Patrick J. Deneen requires readers to rethink the issues that are truly at the heart of our contemporary 'Culture Wars,' and he encourages us to reassess our assumptions about the Western canon's virtues or viciousness. Deneen's penetrating exploration of Odysseus's and our own enduring battles between the dual temptations of homecoming and exploration, patriotism and cosmopolitanism, and relativism and universality provides an original perspective on contentious debates at the center of modern political theory and philosophy.